Consumer Economics of Branding: The Role of Marketing Strategies and Purchase Intention in N’Pure Skincare Purchasing Decisions in Jakarta - Nurhayati, Ayu; Suryono , Imam (Yayasan Riset dan Pengembangan Intelektual, 2025)
The millennial generation in Indonesia is particularly fond of skincare products like Npure. In order to better understand how marketing and branding strategies influence consumers' decisions to buy Npure skincare products, this study aims to clarify the role that purchase intention plays in this process. One hundred residents of DKI Jakarta were chosen as research samples for this study using a purposive sampling approach. In this study, data was gathered using online surveys that were analysed using SmartPLS software and the PLS-SEM technique. This study found that the marketing approach for Npure skincare products increased interest in purchasing these items. Branding methods have a detrimental effect on consumers' decisions to buy Npure skincare products, according to this study. In addition, the study's findings show that marketing tactics have a stronger impact on consumers' decisions to purchase Npure skincare products when purchase interest acts as a positive moderator. Similarly, with Npure skincare goods, the presence of purchase interest can fully mitigate the impact of branding techniques on consumers' inclinations to buy